CONTEXTUALIZATION OF THE HADITH OF SAYING SALAM AGAINST NON MUSLIMS (APPLICATION OF FAZLUR RAHMAN'S DOUBLE MOVEMENT THEORY): CONTEXTUALIZATION OF THE HADITH OF SAYING SALAM AGAINST NON MUSLIMS (APPLICATION OF FAZLUR RAHMAN'S DOUBLE MOVEMENT THEORY) - Vanesa; Hasanah, Uswatun; Nadhiran, Hedhri (Taqrib : Journal of Islamic Studies and Education, 2023)
Abstract The research entitled “Contextualiazation of Hadith Saying Greeting to No Muslims (Aplication of Fazlur Rahman’s Double Movement Theory)” is motivated by the existence of modern associations that trigger social phenomena, namely phenomena and responding to greetings from non-Muslims. This phenomena occurs because of doubts and habit or tradition of the community in greeting norms, giving rise to various perspectives. While in religion it has been clearly explained that there is a barrier in the context between Muslims and Non Muslims. The existence of these problems raises the questions of how the understanding of the hadith regarding how to greet non Muslims? And how is the contextualization of the hadith in the present?. This seeks to determine how perceptions of hadiths greets non Muslim and I contextualized through Fazlur Rahman’s Double Movement theory, using Library Research method. In addition to collecting data obtained from documentation or literature and interview as supporting data in this study.